Taá¹wÄ«ru WasÄ«lah at-Taâ€˜lÄ«mu LimahÄrati al-QirÄâ€™ah â€˜Abru NizÄmi IdÄrati at-Taâ€˜allumi (LMS) Moodle FÄ« al-Madrasah aá¹¡-á¹ anÄwiyyah al-HukÅ«miyyah al-â€™Ula Situbondo: Development of Learning Media for Maharah Kalam Through LMS Moodle at Man 1 Situbondo - Ahmad Fajri Fadhili; Muhammad Syaiful Bahri Hidayat (al MahÄra: Jurnal Pendidikan Bahasa Arab, 2023)
Learning during the pandemic demands to be more creative and innovative. However, the problem at school is that teachers have not been able to realize optimal learning because there is no adequate media. In connection with this, the researchers intend to develop learning media. This study aims 1) to describe the development of learning media-based (LMS Moodle) in learning reading skills through E-learning at MAN 1 Situbondo, 2) to analyze the feasibility of developing learning media based (LMS Moodle) in learning reading skills through E-learning at MAN 1 Situbondo, 3) to measure the effectiveness of the use of media-based learning (LMS Moodle) in learning reading skills through E-learning at MAN 1 Situbondo.This study uses a research and development (R&D) approach. The development steps used in this research are research steps according to "Borg and Gall". Data collection techniques are observation, interviews, questionnaires, tests. While the data sources are teachers and students, with a sample of 24 students.The results of this study are: 1) the development process in this study produces products that are in accordance with the needs of the MAN 1 Situbondoschool, especially learning Arabic. 2) validation was carried out on media and materials expert validators and showed that the developed media obtained values of 95% and 82%, respectively. This the developed media meets the valid category. 3) Wilcoxson test results show that Asymp. Sig. (2-tailed) is 0.000. This shows that the developed media is suitable for use in the learning process at school. Keywords: Learning Media, Reading, LMS Moodle, E-Learning Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â  Ù…Ù„Ø®Øµ ÙŠØªØ·Ù„Ø¨ Ø§Ù„ØªØ¹Ù„ÙŠÙ… Ø£Ø«Ù†Ø§Ø¡ Ø§Ù„ÙˆØ¨Ø§Ø¡ Ø£Ù† ÙŠÙƒÙˆÙ† Ø£ÙƒØ«Ø± Ø¥Ø¨Ø¯Ø§Ø¹Ù‹Ø§ ÙˆØ§Ø¨ØªÙƒØ§Ø±Ù‹Ø§. ÙˆÙ…Ø¹ Ø°Ù„ÙƒØŒ ÙØ¥Ù† Ø§Ù„Ù…Ø´ÙƒÙ„Ø© ÙÙŠ Ø§Ù„Ù…Ø¯Ø±Ø³Ø© Ù‡ÙŠ Ø£Ù† Ø§Ù„Ù…Ø¹Ù„Ù…ÙŠÙ† Ù„Ù… ÙŠØªÙ…ÙƒÙ†ÙˆØ§ Ù…Ù† ØªØÙ‚ÙŠÙ‚ Ø§Ù„ØªØ¹Ù„Ù… Ø§Ù„Ø£Ù…Ø«Ù„ Ø¨Ø³Ø¨Ø¨ Ø¹Ø¯Ù… ÙˆØ¬ÙˆØ¯ ÙˆØ³Ø§Ø¦Ù„ Ù…Ù†Ø§Ø³Ø¨Ø©. ÙÙŠ Ù‡Ø°Ø§ Ø§Ù„ØµØ¯Ø¯ØŒ ÙŠØ¹ØªØ²Ù… Ø§Ù„Ø¨Ø§ØØ« ØªØ·ÙˆÙŠØ± ÙˆØ³Ø§Ø¦Ù„ Ø§Ù„ØªØ¹Ù„ÙŠÙ…. ØªÙ‡Ø¯Ù Ù‡Ø°Ù‡ Ø§Ù„Ø¯Ø±Ø§Ø³Ø© Ø¥Ù„Ù‰ 1) ÙˆØµÙ ØªØ·ÙˆÙŠØ± ÙˆØ³Ø§Ø¦Ù„ Ø§Ù„ØªØ¹Ù„Ù…ÙŠ Ø§Ù„Ù‚Ø§Ø¦Ù…Ø© Ø¹Ù„Ù‰ Ø§Ù„ØªØ¹Ù„ÙŠÙ… (LMS Moodle) ÙÙŠ ØªØ¹Ù„ÙŠÙ… Ù…Ù‡Ø§Ø±Ø§Øª Ø§Ù„Ù‚Ø±Ø§Ø¡Ø© Ù…Ù† Ø®Ù„Ø§Ù„ Ø§Ù„ØªØ¹Ù„ÙŠÙ… Ø§Ù„Ø¥Ù„ÙƒØªØ±ÙˆÙ†ÙŠ ÙÙŠ Ø§Ù„Ù…Ø¯Ø±Ø³Ø© Ø§Ù„Ø«Ø§Ù†ÙˆÙŠØ© Ø§Ù„ØÙƒÙˆÙ…ÙŠØ© Ø§Ù„Ø£ÙˆÙ„Ù‰ Ø³ÙŠØªÙˆØ¨ÙˆÙ†Ø¯ÙˆØŒ 2) Ù„ØªØÙ„ÙŠÙ„ ØµÙ„Ø§ØÙŠØ© ØªØ·ÙˆÙŠØ± ÙˆØ³Ø§Ø¦Ù„ Ø§Ù„ØªØ¹Ù„ÙŠÙ… Ø§Ù„Ù‚Ø§Ø¦Ù…Ø© Ø¹Ù„Ù‰ Ø§Ù„ØªØ¹Ù„ÙŠÙ… (LMS Moodle) ÙÙŠ ØªØ¹Ù„Ù… Ù…Ù‡Ø§Ø±Ø§Øª Ø§Ù„Ù‚Ø±Ø§Ø¡Ø© Ù…Ù† Ø®Ù„Ø§Ù„ Ø§Ù„ØªØ¹Ù„Ù… Ø§Ù„Ø¥Ù„ÙƒØªØ±ÙˆÙ†ÙŠ ÙÙŠ Ø§Ù„Ù…Ø¯Ø±Ø³Ø© Ø§Ù„Ø«Ø§Ù†ÙˆÙŠØ© Ø§Ù„ØÙƒÙˆÙ…ÙŠØ© Ø§Ù„Ø£ÙˆÙ„Ù‰ Ø³ÙŠØªÙˆØ¨ÙˆÙ†Ø¯ÙˆØŒ3) Ù„Ù‚ÙŠØ§Ø³ ÙØ¹Ø§Ù„ÙŠØ© Ø§Ù„ØªØ¹Ù„ÙŠÙ… Ø§Ù„Ù‚Ø§Ø¦Ù… Ø¹Ù„Ù‰ Ø§Ù„ÙˆØ³Ø§Ø¦Ù„ (LMS Moodle) ÙÙŠ ØªØ¹Ù„ÙŠÙ… Ù…Ù‡Ø§Ø±Ø§Ø© Ø§Ù„Ù‚Ø±Ø§Ø¡Ø© Ù…Ù† Ø®Ù„Ø§Ù„ Ø§Ù„ØªØ¹Ù„ÙŠÙ… Ø§Ù„Ø¥Ù„ÙƒØªØ±ÙˆÙ†ÙŠ ÙÙŠ Ø§Ù„Ù…Ø¯Ø±Ø³Ø© Ø§Ù„Ø«Ø§Ù†ÙˆÙŠØ© Ø§Ù„ØÙƒÙˆÙ…ÙŠØ© Ø§Ù„Ø£ÙˆÙ„Ù‰ Ø³ÙŠØªÙˆØ¨ÙˆÙ†Ø¯Ùˆ. ØªØ³ØªØ®Ø¯Ù… Ù‡Ø°Ù‡ Ø§Ù„Ø¯Ø±Ø§Ø³Ø© Ù…Ù†Ù‡Ø¬ Ø§Ù„Ø¨ØØ« ÙˆØ§Ù„ØªØ·ÙˆÙŠØ± (R & D). Ø®Ø·ÙˆØ§Øª Ø§Ù„ØªØ·ÙˆÙŠØ± Ø§Ù„Ù…Ø³ØªØ®Ø¯Ù…Ø© ÙÙŠ Ù‡Ø°Ø§ Ø§Ù„Ø¨ØØ« Ù‡ÙŠ Ø®Ø·ÙˆØ§Øª Ø¨ØØ« ØØ³Ø¨ "Borg and Gall". Ø£Ø³Ù„ÙˆØ¨ Ø¬Ù…Ø¹ Ø§Ù„Ø¨ÙŠØ§Ù†Ø§Øª Ù‡ÙŠ Ø§Ù„Ù…Ù„Ø§ØØ¸Ø© ÙˆØ§Ù„Ù…Ù‚Ø§Ø¨Ù„Ø§Øª ÙˆØ§Ù„Ø§Ø³ØªØ¨ÙŠØ§Ù†Ø§Øª ÙˆØ§Ù„Ø§Ø®ØªØ¨Ø§Ø±Ø§Øª. ÙÙŠ ØÙŠÙ† Ø£Ù† Ù…ØµØ§Ø¯Ø± Ø§Ù„Ø¨ÙŠØ§Ù†Ø§Øª Ù‡ÙŠ Ø§Ù„Ù…Ø¹Ù„Ù…Â  ÙˆØ§Ù„Ø·Ù„Ø§Ø¨ Ø¨Ø¹ÙŠÙ†Ø© Ù…Ù† 24 Ø·Ø§Ù„Ø¨Ù‹Ø§. Ù†ØªØ§Ø¦Ø¬ Ù‡Ø°Ù‡ Ø§Ù„Ø¯Ø±Ø§Ø³Ø© Ù‡ÙŠ: 1) ØªÙ†ØªØ¬ Ø¹Ù…Ù„ÙŠØ© Ø§Ù„ØªØ·ÙˆÙŠØ± ÙÙŠ Ù‡Ø°Ù‡ Ø§Ù„Ø¯Ø±Ø§Ø³Ø© Ù…Ù†ØªØ¬Ø§Øª ØªØªÙˆØ§ÙÙ‚ Ù…Ø¹ Ø§ØØªÙŠØ§Ø¬Ø§Øª Ù…Ø¯Ø±Ø³Ø© Ø§Ù„Ø«Ø§Ù†ÙˆÙŠØ© Ø§Ù„Ø£ÙˆÙ„Ù‰ Ø³ÙŠØªÙˆØ¨ÙˆÙ†Ø¯Ùˆ ØŒ ÙˆØ®Ø§ØµØ© ØªØ¹Ù„ÙŠÙ… Ø§Ù„Ù„ØºØ© Ø§Ù„Ø¹Ø±Ø¨ÙŠØ©. 2) ØªÙ… Ø¥Ø¬Ø±Ø§Ø¡ Ø§Ù„ØªØÙ‚Ù‚ Ù…Ù† ØµØØ© Ø§Ù„ÙˆØ³Ø§Ø¦Ø· ÙˆØ§Ù„Ù…ÙˆØ§Ø¯ Ø§Ù„Ù…Ø¯Ù‚Ù‚Ø© ÙˆØ£Ø¸Ù‡Ø± Ø£Ù† Ø§Ù„ÙˆØ³Ø§Ø¦Ø· Ø§Ù„Ù…Ø·ÙˆØ±Ø© ØØµÙ„Øª Ø¹Ù„Ù‰ Ù‚ÙŠÙ… 95Ùª Ùˆ 82Ùª Ø¹Ù„Ù‰ Ø§Ù„ØªÙˆØ§Ù„ÙŠ. ÙˆØ¨Ø§Ù„ØªØ§Ù„ÙŠ ÙØ¥Ù† Ø§Ù„ÙˆØ³Ø§Ø¦Ø· Ø§Ù„Ù…ØªØ·ÙˆØ±Ø© ØªÙ„Ø¨ÙŠ Ø§Ù„ÙØ¦Ø© Ø§Ù„ØµØ§Ù„ØØ©. 3) ØªØ¸Ù‡Ø± Ù†ØªØ§Ø¦Ø¬ Ø§Ø®ØªØ¨Ø§Ø± ÙˆÙŠÙ„ÙƒÙˆÙƒØ³ÙˆÙ† Ø£Ù† Asymp. Ø³ÙŠØ¬. (2-tailed) ØªØ³Ø§ÙˆÙŠ 0.000. Ù‡Ø°Ø§ ÙŠØ¯Ù„ Ø¹Ù„Ù‰ Ø£Ù† Ø§Ù„ÙˆØ³Ø§Ø¦Ù„ Ø§Ù„Ù…Ø·ÙˆÙ‘Ø±Ø© Ù…Ù†Ø§Ø³Ø¨Ø© Ù„Ù„Ø§Ø³ØªØ®Ø¯Ø§Ù… ÙÙŠ Ø¹Ù…Ù„ÙŠØ© Ø§Ù„ØªØ¹Ù„Ù‘Ù… ÙÙŠ Ø§Ù„Ù…Ø¯Ø±Ø³Ø©. Ø§Ù„ÙƒÙ„Ù…Ø§Øª Ø§Ù„Ù…ÙØªØ§ØÙŠØ©: Ø§Ù„ÙˆØ³Ø§Ø¦Ù„ Ø§Ù„ØªØ¹Ù„ÙŠÙ…ÙŠØ©ØŒ Ù…Ù‡Ø§Ø±Ø© Ø§Ù„Ù‚Ø±Ø§Ø¡Ø©